SELF DISCLOSURE PENGGUNA INSTAGRAM STORIES OLEH GENERASI Z DI KOTA PADANG - Akhsanul Pikri; Ringgo Eldapi Yozani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The use of social media, especially Instagram stories among Generation Z is to expand relationships in cyberspace without any limitations. They also do not have any obstacles in the virtual world because their lives can be very different between the real world and the virtual world. The act of self-disclosure through Instagram Stories is done by uploading photos, videos, and in the form of text. This study aims to find out how the form of self-disclosure through the aspects of selfdisclosure of Generation Z in Padang City through Instagram Stories. This study uses the theory of self-disclosure (Johari Window). This study uses a type of qualitative research with a phenomenological approach. The subject of this research is Generation Z in Padang City, then the researcher selects the informants according to the criteria of the informants to be studied. The informants in this study were six informants. Data collection techniques using observation, interviews, and documentation. Based on the results regarding self-disclosure, it can be concluded that the self-disclosure carried out by Generation Z in Padang City through Instagram stories which are included in Johari's three windows are open areas, blind areas, and hidden areas. Self-disclosure means disclosing, informing, and sharing moments or information with others, both private and public. There are two impacts that Generation Z gets in carrying out self-disclosure through Instagram Stories, namely positive and negative impacts and there are four goals of Generation Z in Padang City to carry out self-disclosure, namely, to express themselves, motivate others, show off, and share information. The tendency of their goal of selfdisclosure is to express themselves. Self-disclosure by Generation Z in Padang City through Instagram Stories is mostly done in a hidden form. Researchers found that the informants studied did not openly self-disclosure, they were wiser in expressing themselves and filtered and sorted out first which ones were good to upload or share and which ones deserved to be uploaded in their Instagram stories. Keywords: Self Disclosure, Media Social, Z Generation